Improving the story-telling skill of grade 1 students through the use of hand puppet media - Siti Zuraidah; Kastam Syamsi; Ashadi Ashadi (Jurnal Prima Edukasia, 2020)
The purpose of this study is to improve the storytelling skills in language learning  of grade I students of Muhammadiyah Elementary School Sapen Yogyakarta using hand puppet media.This research is collaborative classroom action research with the cycle model design. The subject of the study was grade I students of Al Ibadi Muhammadiyah Elementary School Sapen, totaling 30 students, consisting of 16 male and 14 female students. The data were collected through observatioThe purpose of this study is to improve the storytelling skills in language learning  of grade I students of Muhammadiyah Elementary School Sapen Yogyakarta using hand puppet media.This research is collaborative classroom action research with the cycle model design. The subject of the study was grade I students of Al Ibadi Muhammadiyah Elementary School Sapen, totaling 30 students, consisting of 16 male and 14 female students. The data were collected through observation and documentation as well as using a questionnaire and test, and analyzed using the descriptive qualitative and quantitative analysis.The results show that the use of hand puppet media in Indonesian language learning could improve the storytelling skill of grade 1 students. This is evidenced by the increase in the students’ average score and minimum mastery in their storytelling skills. The students’ mean score increased from 62 in Cycle 1 to 80 in Cycle 2. Likewise, the percentage of the students with minimum mastery increased from 40% (12 students) in Cycle 1 to 87% (26 students) in Cycle 2.n and documentation as well as using a questionnaire and test, and analyzed using the descriptive qualitative and quantitative analysis.The results show that the use of hand puppet media in Indonesian language learning could improve the storytelling skill of grade 1 students. This is evidenced by the increase in the students’ average score and minimum mastery in their storytelling skills. The students’ mean score increased from 62 in Cycle 1 to 80 in Cycle 2. Likewise, the percentage of the students with minimum mastery increased from 40% (12 students) in Cycle 1 to 87% (26 students) in Cycle 2.